A Soft-5/6 Modulation Code with Iterative ITI Subtraction Scheme in Multireader TDMR Systems - Pituso, Kotchakorn; Warisarn, Chanon; Tongsomporn, Damrongsak (My University, 2017)
The huge growth of the consumer electronic industry is driving the need for achieving ultrahigh areal storage densities. 2-D magnetic recording is a promising high-density storage technology where the shingled writing technique is employed for increasing the track per inch (TPI) and achieving higher areal densities. Nevertheless, high TPI causes a reader to cover higher number of tracks, which leads to the intertrack interference (ITI); hence the system performance is severely deteriorated. Therefore, we first propose the soft-5/6 modulation code together with iterative ITI subtraction scheme. Here, the soft information encoding and decoding schemes operate based on Boolean logic circuit for using in the iterative system. Furthermore, we also propose to move the upper and lower readers closer to the center reader to avoid the ITI effect from their outer tracks, which will then be performed together with ITI subtraction scheme. Moreover, this proposed reading technique is also applied together with the soft-4/5 modulation code. The simulation results show that the proposed systems are superior to the conventional system, especially at high user density.
Keywords: 2-D magnetic recording (TDMR); 2-D modulation code; intertrack interference (ITI)